2022
DOI: 10.3390/ijerph19159048
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Delayed Initiation of Breastfeeding: A Cross-Sectional Multicenter Study in Abu Dhabi, the United Arab Emirates

Abstract: One of the best practices to reduce the risk of infant morbidity and mortality is the early initiation of breastfeeding, specifically within the first hour of birth, as the World Health Organization (WHO) recommends. Limited data exist on breastfeeding initiation and its related factors in the United Arab Emirates (U.A.E.). Therefore, the purpose of this research study was to evaluate and analyze the determinant factors associated with delayed initiation of breastfeeding among mothers with children aged <2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
0
1
Order By: Relevance
“…In contrast, this finding is lower than the rates found in previous studies in Ethiopia, specifically in Arba Minch Zuria (57.2%)53 and Debre Berhan town (37.4%) 31. Additionally, the prevalence observed in this study is lower than the rates reported in the United Arab Emirates (37%),54 Tanzania (49%),35 Brazil (52.9%),55 Nigeria (65.3%)56 and Bangladesh (61.5%). This discrepancy might be attributed to variations in the use of healthcare services, community wealth level, culture, taboos towards the first breast milk (colostrum), religion and methodology between studies.…”
Section: Discussioncontrasting
confidence: 93%
“…In contrast, this finding is lower than the rates found in previous studies in Ethiopia, specifically in Arba Minch Zuria (57.2%)53 and Debre Berhan town (37.4%) 31. Additionally, the prevalence observed in this study is lower than the rates reported in the United Arab Emirates (37%),54 Tanzania (49%),35 Brazil (52.9%),55 Nigeria (65.3%)56 and Bangladesh (61.5%). This discrepancy might be attributed to variations in the use of healthcare services, community wealth level, culture, taboos towards the first breast milk (colostrum), religion and methodology between studies.…”
Section: Discussioncontrasting
confidence: 93%